Pediatric Reference Intervals for Critical Point-of-Care Whole Blood Assays in the CALIPER Cohort of Healthy Children and Adolescents. Issue 6 (29th May 2021) - Bohn, Mary Kathryn; Hall, Alexandra; Wilson, Siobhan; Henderson, Tina; Adeli, Khosrow
Abstract: Objectives: Point-of-care testing (POCT) is being increasingly adopted to support clinical care. Data for critical care parameters in healthy children on POCT instruments are lacking. We established comprehensive reference standards for several whole blood parameters on the Radiometer ABL90 FLEX PLUS blood gas analyzer in the Canadian Laboratory Initiative on Paediatric Reference Intervals (CALIPER) cohort. Methods: Approximately 300 healthy children and adolescents (age range, birth to <19 years; sex, boys and girls) were recruited with informed consent. Venous whole blood was collected (using heparinized syringes) and rapidly analyzed at the point of collection for pH, Pco 2, Po 2, carboxyhemoglobin, methemoglobin, lactate, and electrolytes on the ABL90 FLEX PLUS instrument. Reference intervals were established according to Clinical and Laboratory Standards Institute guidelines. Results: Of the parameters assessed, 6 required age partitioning; none required sex partitioning. Reference value distributions were consistent across the pediatric age range, demonstrating higher variation in the early neonatal period. Conclusions: This study established reference standards for 10 critical care analytes in the CALIPER cohort for the first time. These data contribute to our understanding of normative pediatric values for venous electrolytes, metabolites, and blood gases on a modern POCT instrument, facilitating test interpretation in clinical settings that use these assays.